Peran Pendidikan Agama Islam dalam Menangkal Dampak Negatif Media Sosial pada Remaja di Pacitan - Muqsonah, Nely Badiya; Hudha, Mokhamad Choirul (ALSYS, 2025)
This research investigates the pervasive influence of social media, particularly Instagram and TikTok, on the moral and ethical values of teenagers in Pacitan. The purpose of this study is to evaluate the role of Islamic Religious Education (PAI) in mitigating the adverse effects of social media on this demographic. Employing a descriptive qualitative methodology, data were collected through questionnaires administered to junior high school students across three schools in Pacitan. The findings reveal that PAI instruction significantly contributes to the development of social media ethics aligned with Islamic principles, enhances character formation, and fosters spiritual awareness among adolescents. Additionally, the involvement of teachers and parents emerged as crucial supporting factors in this educational endeavor. This study advocates for the reinforcement of the PAI curriculum through the integration of digital literacy, thereby equipping students to navigate the complexities of the digital age effectively. The broader implications of these findings underscore the necessity for educational institutions to adapt their curricula in response to the challenges posed by social media, ultimately fostering a more ethically aware and resilient youth population.